Thank you : saying thanks to ... everything! - Jarvis, 1985- (Candlewick Press, 2024)
"The moon brings nighttime, and the sun the day. With no yellow and blue, we'd be a world without green lights, and without itches we'd never know the relief of a scratch. From oversized plants that offer hiding places to boots that somehow know the way, from siblings who bravely take the first plunge to yourself for being you, award-winning picture-book creator Jarvis spans the gamut from the silly to the sublime and opens the endless possibilities for giving thanks."--